2019
DOI: 10.1002/ppul.24440
|View full text |Cite
|
Sign up to set email alerts
|

Are home sleep studies useful in diagnosing obstructive sleep apnea in children with down syndrome?

Abstract: Introduction and Aim Obstructive sleep apnea syndrome (OSAS) is frequent in children with Down syndrome (DS) and polysomnography (PSG) is recommended for all children with DS. However PSG is not always available and alternative diagnostic methods are needed. The aim of the study was to evaluate the feasibility and validity of home polygraphy (HPG) in children with DS. Methods A national DS association was contacted and children aged 6 to 18 years who accepted to participate were recruited. Otorhinolaryngologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Polygraphy for children with DS shows a slightly lower OSA prevalence than polysomnography [ 38 ]. Sensitivity and specificity of polygraphy were higher when diagnosing moderate to severe OSA [ 50 ]. Validation of this test in adults with DS has not yet been performed.…”
Section: Sleep Disordersmentioning
confidence: 99%
“…Polygraphy for children with DS shows a slightly lower OSA prevalence than polysomnography [ 38 ]. Sensitivity and specificity of polygraphy were higher when diagnosing moderate to severe OSA [ 50 ]. Validation of this test in adults with DS has not yet been performed.…”
Section: Sleep Disordersmentioning
confidence: 99%
“…Down syndrome (DS), which is caused by an additional copy of chromosome 21, is the most common chromosomal abnormality in children, occurring in an estimated one in 700 births [ 1 – 5 ]. Obstructive sleep apnea (OSA) is a frequent condition in people with DS, with an estimated rate between 55 and 97% [ 2 , 6 , 7 ]. There are many underlying predisposing factors for OSA in DS such as midfacial hypoplasia, relative macroglossia, glossoptosis, pharyngeal hypotonia, tonsillar hypertrophy, laryngomalacia, and obesity [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A multicenter study investigated the use of home pulse oximetry (HPO) to identify children with DS at increased risk for OSA and reported a sensitivity for moderate-to-severe OSA up to 96% depending on the HPO parameters used [29]. The use of home polygraphy has also garnered interest, and one study in children with DS reported a 100% sensitivity and 83% specificity when AHI ≥ 3 was used for the diagnosis of OSA [30]. This will likely miss mild OSA, and it has not yet been determined at what threshold OSA results in sequalae.…”
Section: Diagnosismentioning
confidence: 99%